THE INFLUENCE OF THE PRINCIPAL'S LEADERSHIP IN IMPROVING TEACHER PERFORMANCE - Yulidarna; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In the learning process teachers are seen as having an important role, especially in helping students to develop their potential in cognitive, affective and psychomotor abilities. Teacher performance can be seen and measured based on the specifications / competency criteria that must be possessed by each teacher. Can be displayed through mastery of pedagogic, professional, personality and social competencies. This study aims to: 1) determine whether or not there is an influence of the principal's leadership on improving teacher performance; 2) Knowing whether or not there is an effect of improvement on teacher performance. The research method used is quantitative method. The results of this study show that: 3) there is a very significant positive influence between the influence of the principal's leadership on improving teacher performance; 4) There is a very significant positive influence between improvements in teacher performance. Teacher performance will increase if the teacher has carried out elements consisting of loyalty and high commitment to the task of teaching, mastering and developing learning materials, discipline in teaching and other tasks